Effects of Different Stimulation Conditions on the Stimulation Effect of Noisy Galvanic Vestibular Stimulation - Inukai, Yasuto; Miyaguchi, Shota; Saito, Miki; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Human Neuroscience, 2020)
Balance disorders are a risk factor for falls in the elderly population. Balance control involving the complex interaction among nervous, muscular, and sensory systems should be maintained to keep an upright posture and prevent falls. Vestibular sensation is one of the main senses essential for postural control. Noisy galvanic vestibular stimulation (nGVS) is a noninvasive stimulation method for vestibular organs. Recently, it has received increasing attention for the treatment of balance disorders. However, the effect of balance disorders on stimulus effect during the implementation of nGVS remains unknown. Therefore, this study aimed to determine the effects of different floor surface and visual conditions on the stimulus effects of the nGVS intervention. In this study, two experiments were conducted with 24 participants (12 each for Experiments 1 and 2). In Experiment 1, nGVS (0.4 mA; 0.1–640 Hz) was performed in the open-eyes standing position on a solid surface (nGVS condition) and in the closed-eye standing position on a foam rubber (nGVS + foam rubber condition). In Experiment 2, sham stimulation was performed under the same conditions as in Experiment 1, except for nGVS. Center of pressure (COP) sway was measured in all participants with them standing with open eyes at Pre and Post-1 (immediately after the intervention) and Post-2 (10 min after the measurement of post-1). In Experiment 1, under the nGVS condition, COP sway was significantly reduced in Post-1 and Post-2 compared with Pre. However, no significant difference was observed among Pre, Post-1, and Post-2 under the nGVS + foam rubber condition. Furthermore, the intervention effect was significantly greater in the nGVS condition than in the nGVS + foam rubber condition. In contrast, in Experiment 2, the COP sway did not significantly differ among Pre, Post-1, and Post-2 under either condition. Based on the results of this study, nGVS was found to be effective with open-eyes standing on a solid surface.